Entomological survey of sibling species in the Anopheles funestus group in Tanzania confirms the role of Anopheles parensis as a secondary malaria vector - Mapua, Salum Abdallah; Samb, Badara; Nambunga, Ismail Hassan; Mkandawile, Gustav; Bwanaly, Hamis; Kaindoa, Emmanuel Wilson; Odero, Joel Ouma; Masalu, John Paliga; Kahamba, Najat Feruz; Hape, Emmanuel Elirehema; Govella, Nicodem James; Okumu, Fredros Oketch; et al. (Parasites & vectors, 2024)
Background Malaria transmission in Tanzania is driven by mosquitoes of the Anopheles gambiae complex and Anopheles funestus group. The latter includes An . funestus s.s., an anthropophilic vector, which is now strongly resistant to public health insecticides, and several sibling species, which remain largely understudied despite their potential as secondary vectors. This paper provides the initial results of a cross-country study of the species composition, distribution and malaria transmission potential of members of the Anopheles funestus group in Tanzania. Methods Mosquitoes were collected inside homes in 12 regions across Tanzania between 2018 and 2022 using Centres for Disease Control and Prevention (CDC) light traps and Prokopack aspirators. Polymerase chain reaction (PCR) assays targeting the noncoding internal transcribed spacer 2 (ITS2) and 18S ribosomal DNA (18S rDNA) were used to identify sibling species in the An . funestus group and presence of Plasmodium infections, respectively. Where DNA fragments failed to amplify during PCR, we sequenced the ITS2 region to identify any polymorphisms. Results The following sibling species of the An . funestus group were found across Tanzania: An . funestus s.s. (50.3%), An . parensis (11.4%), An . rivulorum (1.1%), An . leesoni (0.3%). Sequencing of the ITS2 region in the nonamplified samples showed that polymorphisms at the priming sites of standard species-specific primers obstructed PCR amplification, although the ITS2 sequences closely matched those of An . funestus s.s., barring these polymorphisms. Of the 914 samples tested for Plasmodium infections, 11 An . funestus s.s. (1.2%), and 2 An . parensis (0.2%) individuals were confirmed positive for P . falciparum . The highest malaria transmission intensities [entomological inoculation rate (EIR)] contributed by the Funestus group were in the north-western region [108.3 infectious bites/person/year (ib/p/y)] and the south-eastern region (72.2 ib/p/y). Conclusions Whereas An . funestus s.s. is the dominant malaria vector in the Funestus group in Tanzania, this survey confirms the occurrence of Plasmodium -infected An . parensis , an observation previously made in at least two other occasions in the country. The findings indicate the need to better understand the ecology and vectorial capacity of this and other secondary malaria vectors in the region to improve malaria control. Graphical Abstract